A cure for discrimination? Affirmative action and the case of California Proposition 209 - Caitlin Knowles Myers (Institute for the Study of Labor (IZA), 2005)
Proposition 209, enacted in California in 1996 and made effective the following year, ended state affirmative action programs not only in education, but also for public employment and government contracting. This paper uses CPS data and triple difference techniques to take advantage of the natural experiment presented by this change in state law to gauge the labor market impacts of ending affirmative action programs. Employment among women and minorities dropped sharply, a change that was nearly completely explained by a decline in participation rather than by increases in unemployment. This decline suggests that either affirmative action programs in California had been inefficient or that they failed to create lasting change in prejudicial attitudes.
Keywords: J71; J78; 330; economics of gender and minorities; affirmative action; Proposition 209; discrimination